2021
DOI: 10.1016/j.jamda.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Home-Based Physical Exercise on Days at Home and Cost-Effectiveness in Pre-Frail and Frail Persons: Randomized Controlled Trial

Abstract: Twelve-month supervised home-based exercise had no effect on days lived at home vs. usual care in cases of frailty. It prevented decline in quality-of-life. The first years' increased healthcare costs were regained over the next year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Eighty four (84) full-text studies were assessed for eligibility. Following further eliminations based on the inclusion and exclusion criteria, only 14 studies [ 13 26 ] were finally included in this analysis. A flow diagram of the study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty four (84) full-text studies were assessed for eligibility. Following further eliminations based on the inclusion and exclusion criteria, only 14 studies [ 13 26 ] were finally included in this analysis. A flow diagram of the study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Physical exercise has always contributed to good health. A recent study assessing the effect of home-based physical exercise on days at home in pre-frail and frail persons showed exercise intervention to prevent the deterioration of health-related quality of life [ 26 ]. Another randomized trial demonstrating the effect of resistance exercise on frailty and functional health in community-dwelling older adults showed a 3-month multifactorial intervention to have reduced frailty and improved functional health, and these effects persisted for at least 3 more months after the exercise intervention [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol has been published, 14 and the primary outcome, days lived at home, has been reported earlier. 15 In short, we performed a parallel, randomized clinical trial, with a 1:1 allocation ratio. After the baseline assessments, the research personnel randomized participants into two groups, using a computer-generated random sequence allocation program with randomly varying block sizes from 2 to 10, without stratification.…”
Section: Methodsmentioning
confidence: 99%
“…frail or prefrail) older adults have been conducted around the world, including in China. Among these studies, well‐accepted physical frailty measures, including Physical Frailty Phenotype (PFP) (Cameron et al, 2013; Chan et al, 2012; Chen et al, 2020; Fairhall et al, 2014; Hsieh et al, 2019; Kang et al, 2019; Kim et al, 2015; Lai et al, 2021; Liao et al, 2021; Liu et al, 2021; Losa‐Reyna et al, 2019; Meng et al, 2020; Ng et al, 2017; Sadjapong et al, 2020; Sanchis et al, 2021; Tarazona‐Santabalbina et al, 2016), Frailty Instrument of Survey of Health Ageing and Retirement in Europe (SHARE‐FI) (Haider et al, 2017; Kapan et al, 2017; Luger et al, 2016) and the FRAIL scale (Lee et al, 2021; Suikkanen et al, 2021a; Suikkanen et al, 2021b; Yu et al, 2020) have been widely used to identify frailty, which may improve the homogeneity in study populations. Prefrailty has been considered as an intervention window, because prefrail older adults are more likely to transit back to a robust state through appropriate interventions compared with those who are frail (Bray et al, 2016; Frost et al, 2017; Gwyther et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of outcome measurement does matter in an intervention study. Previous studies primarily focus on the intervention effectiveness on frailty, muscle outcomes (mass, strength and physical performance), falls and physical functional abilities, but ignore intervention effects on mental and social functioning (Cameron et al, 2013; Chan et al, 2012; Chen et al, 2020; Clegg et al, 2014; Fairhall et al, 2014; Haider et al, 2017; Hsieh et al, 2019; Jadczak et al, 2018; Kang et al, 2019; Kapan et al, 2017; Kim et al, 2015; Kwon et al, 2015; Lai et al, 2021; Liu et al, 2021; Losa‐Reyna et al, 2019; Luger et al, 2016; Meng et al, 2020; Sadjapong et al, 2020; Sanchis et al, 2021; Suikkanen et al, 2021a; Suikkanen et al, 2021b; Tarazona‐Santabalbina et al, 2016; Yu et al, 2020). Essentially, researchers are encouraged to investigate the effectiveness of exercise interventions from a broad perspective for comprehensive effectiveness evaluation, because exercise interventions have the potential to improve physical, mental and social functioning (Dedeyne et al, 2017; Garcia‐Hermoso et al, 2020; Tarazona‐Santabalbina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%